2018
DOI: 10.1080/17843286.2018.1511264
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic joint infection caused byCandida lusitaniae: report of a unique case

Abstract: To our knowledge, this is the first reported case of Candida lusitaniae PJI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Following a thorough electronic literature search of the PubMed and MEDLINE databases, only four other cases of PJIs due to C. lusitaniae in revision knee arthroplasties were identified [ 22 , 23 , 24 , 25 ]. Table 1 highlights the main features of these cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a thorough electronic literature search of the PubMed and MEDLINE databases, only four other cases of PJIs due to C. lusitaniae in revision knee arthroplasties were identified [ 22 , 23 , 24 , 25 ]. Table 1 highlights the main features of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding surgical treatment of PJI due to C. lusitanae , Klatte et al reported one case treated with OSRA, which could be considered a safe procedure, while Hwang et al and Viotti et al have successfully managed two cases with TSRA [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%